A novel one-pot process for near-net-shape fabrication of open-porous resorbable hydroxyapatite/protein composites and in vivo assessment - Mueller, Bent; Koch, Dietmar; Lutz, Rainer; Schlegel, Karl A.; Treccani, Laura; Rezwan, Kurosch (Materials Science and Engineering C, 2014)
We present a mild one-pot freeze gelation process for fabricating near-net, complex-shaped hydroxyapatite scaffolds and to directly incorporate active proteins during scaffold processing. In particular, the direct protein incorporation enables a simultaneous adjustment and control of scaffold microstructure, porosity, resorbability and enhancement of initial mechanical and handling stability. Two proteins, serum albumin and lysozyme, are selected and their effect on scaffold stability and microstructure investigated by biaxial strength tests, electron microscopy, and mercury intrusion porosimetry. The resulting hydroxyapatite/protein composites feature adjustable porosities from 50% to 70% and a mechanical strength ranging from 2 to 6 MPa comparable to that of human spongiosa without any sintering step. Scaffold degradation behaviour and protein release are assessed by in vitro studies. A preliminary in vivo assessment of scaffold biocompatibility and resorption behaviour in adult domestic pigs is discussed. After implantation, composites were resorbed up to 50% after only 4 weeks and up to 65% after 8 weeks. In addition, 14% new bone formation after 4 weeks and 37% after 8 weeks were detected. All these investigations demonstrate the outstanding suitability of the one-pot-process to create, in a customisable and reliable way, biocompatible scaffolds with sufficient mechanical strength for handling and surgical insertion, and for potential use as biodegradable bone substitutes and versatile platform for local drug delivery.
EVALuna2:24389